Indigenous Disseminated Penicillium marneffei Infection in the State of Manipur, India: Report of Four Autochthonous Cases - Singh, P. Narendra (American Society for Microbiology, 1999)
We describe four cases of disseminated infection caused by endemic Penicillium marneffei in human immunodeficiency virus (HIV)-infected patients from the Manipur state of India. The most common clinical features observed were fever, anorexia, weight loss, hepatosplenomegaly, and, more importantly, skin lesions resembling molluscum contagiosum. The diagnosis in each of the four cases was achieved by direct examination of smears, observance of intracellular yeast-like cells multiplying by fission in biopsied tissue from skin lesions, and isolation of the dimorphic P. marneffei in pure culture in each case. In one case, fluorescent antibody studies allowed specific diagnosis. This report documents a new area in which P. marneffei is endemic, located in eastern India, and describes the first occurrence in India of P. marneffei in HIV-infected patients as well as the extension of the areas of P. marneffei endemicity westward to the northeastern state of Manipur.